Lanostanoids with acetylcholinesterase inhibitory activity from the mushroom Haddowia longipes. (February 2015) - Zhang, Shuang-Shuang; Ma, Qing-Yun; Huang, Sheng-Zhuo; Dai, Hao-Fu; Guo, Zhi-Kai; Yu, Zhi-Fang; Zhao, You-Xing
Abstract : Graphical abstract: Nine lanostanoids (1–9 ) together with nine known ones were isolated from fungus Haddowia longipes . Thirteen of these compounds possessed substantial inhibitory activity against acetylcholinesterase (AChE). Highlights: First report of lanostanoids isolated from Haddowia longipes. Nine lanostanoids were found in H . longipes. Lanostanoids from H . longipes showed AChE inhibitory activities. Abstract: Nine lanostanoids, together with nine known ones, were isolated from the ethyl acetate extract of the fruiting bodies of the mushroom Haddowia longipes . Their structures were elucidated as 11-oxo-ganoderiol D, lanosta-8-en-7, 11-dioxo-3β-acetyloxy-24, 25, 26-trihydroxy, lanosta-8-en-7-oxo-3β-acetyloxy-11β, 24, 25, 26-tetrahydroxy, lanosta-7, 9(11)-dien-3β-acetyloxy-24, 25, 26-trihydroxy, lanosta-7, 9(11)-dien-3β-acetyloxy-24, 26-dihydroxy-25-methoxy, 11-oxo-lucidadiol, 11β-hydroxy-lucidadiol, lucidone H and lanosta-7, 9(11), 24 E -trien-3β-acetyloxy-26, 27-dihydroxy by analysing their 1D/2D NMR and MS spectra. In addition, bioassays of inhibitory activity against acetylcholinesterase (AChE) of all compounds showed that thirteen compounds possessed inhibitory activity against AChE with the percentage inhibition ranging from 10.3% to 42.1% when tested at 100 μM.